2020
DOI: 10.1021/acsomega.0c02583
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Immobilization in Zinc Oxide Thin Films as an Easy-Handle Strategy for Escherichia coli Detection

Abstract: The antibody immobilization compatible with low-cost materials and label-free strategies is a challenge for biosensor device fabrication. In this study, ZnO thin film deposition was carried out on corning glass substrates by ultrasonic spray pyrolysis at 200 °C. The thin films were analyzed as platforms for enteropathogenic Escherichia coli ( E. coli EPEC) antibody immobilization. The modification of thin films from the functionalization and antibody immobilization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…Nevertheless, ZnO nanostructures are highlighted as promising biosensing candidates due to their structural, optical, and electric properties [86] , [87] , [88] . These materials could be surface engineered for the detection of the SARS-CoV-2 virus, and as mentioned earlier, evidence of this is the pending patent of Thevasahayam et al [23] .…”
Section: A Summary Of Nanomaterials For the Detection Of Covid-19mentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, ZnO nanostructures are highlighted as promising biosensing candidates due to their structural, optical, and electric properties [86] , [87] , [88] . These materials could be surface engineered for the detection of the SARS-CoV-2 virus, and as mentioned earlier, evidence of this is the pending patent of Thevasahayam et al [23] .…”
Section: A Summary Of Nanomaterials For the Detection Of Covid-19mentioning
confidence: 99%
“…Numerous researchers worldwide are currently working on ZnO biosensing maturing projects. In our group, different approaches have been studied recently to observe the influence of morphological properties of these nanostructures for various applications, including bio and gas sensors [87] , [88] , [92] , [93] catalysis [94] , among others. A. Galdamez et al [87] reported the orientations of the Au orchestrated ZnO nanowires (ZnO/Au NWs) on the detection sensitivity of DNA using optical and morphological studies ( Fig.…”
Section: A Summary Of Nanomaterials For the Detection Of Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…The successful modification of the screen-printed electrodes with Pd nanostructures supported onto CNTs demonstrated characteristic vibrations bands at 1511, 1725, and 1227 cm –1 due to the presence of the −CC, −CO, and −C–O functional groups, respectively, from the oxidized CNTs . However, characteristic amide-I stretching (1630 cm –1 ) and amide-II band (1565 cm –1 ) correspond well to the CO stretching of the peptide backbone and bending N–H modes of immobilized anti-HER2 on the Pd-nanostructured surface. , Further, the presence of the target HER2 biomarker showed an increase in the amide-II bands at 1565 cm –1 with a concomitant broadened −NH vibration peak centered at 3315 cm –1 . The observations confirmed the successful fabrication of the Pd-nanostructured immunosensor and its response toward HER2 detection…”
Section: Resultsmentioning
confidence: 96%
“…27 The chemical and physical properties of DNA nanomaterials, such as small size effect and surface effect, are exactly corresponding to the miniaturization and multifunction required by biosensors. 27 Commonly used components in biosensor construction include enzymes, 28 antibodies, 29 nucleic acids, and so on. Among them, aptamer is a kind of oligonucleotide with high affinity and specificity to targets, also known as "chemical antibodies".…”
Section: Introductionmentioning
confidence: 99%